Tazkiyatun Nafs as an Effort to Reduce Premarital Sexual Behavior of Adolescents - Hartati, Sri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2018)
This article describes the concept of tazkiyatun nafs as an effort to reduce premarital sexual behavior of adolescents. Tazkiyatun nafs is assistance provision process that directed, sustained and systematic to individuals in order to develop self-potential optimally through continuous purification of the soul to suppress the bad tendency and develop a good nature to get closer to Allah subhanahu wa ta'ala. This research is focus group discussion type. The results of research stated that tazkiyatun nafs which is used namely ma`rifah, mujahadah, riyadhah and muhasabah. Premarital sexual behavior can result in self-destructive. This can be minimized through the change of rational thinking of individuals who will be aware of the consequences of actions and control of their emotional impulses. People who can control themselves tend to keep away from premarital sexual behavior that is included in the act of adultery. Through tazkiyatun nafs counselees are expected to build ethical behavior as a servant of Allah as well as the khalifah of Allah and able to evaluate the behaviors that are less appropriate through learning to be responsible for what they do which include the consequences of the choices and actions